Empowering parents through early kangaroo mother care a holistic approach to neonatal health: A systematic review - Endah Dessirya; Kusnul Hasanah; Yeni Rustina; Happy Hayati; Mega Hasanul Huda (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: The transition of premature infants from the intrauterine to the extrauterine environment is a complex and challenging adaptation process for infants and their mother. Empowering parents through education and support is crucial in navigating these challenges. Propose: To review parental empowerment through early kangaroo care a holistic approach to neonatal health. Method: Systematic review research according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. This literature research uses seven electronic databases, namely PubMed, Proquest, Sciencedirect, Wiley Online, Emerald insight, Sage Journals, and JSTOR. The data search began on September 30, 2024, using the keywords